ダイ10ジ ナンキョク チイキ カンソクタイ ナイリク チョウサ ガイホウ - 安藤, 久男; アンドウ, ヒサオ; ANDO, Hisao (国立極地研究所, 1971)
P(論文) The oversnow traverse party of the 10th Japanese Antarctic Research Expedition was organized to accomplish the initial stage of scientific programmes of "Glaciological research project of Enderby Land, Antarctica, 1969-1974". The party consists of two geologists, one geomorphologist, two glaciologists, one surgeon, two mechanics, one field assistant, and one cameraman. The party used four oversnow vehicles (two KD-60 and two KC-20), one plywood caravan equipped with six berths and galley, and nine wooden sledges. The maximum load during the traverse was 27 tons. The party left Syowa Station on November 1, 1969 and returned on January 29, 1970, covering the following sites : 69-07S, 42-29E 69-59S, 43-04E 72-00S, 43-09E A-group of Yamato Mountains (71-44S, 35-50E) D-group of Yamato Mountains (71-20S, 35-38E) and 70-51S, 43-07E. Scientific activities of the party were : 1) Astoronomical observation. 2) Barometric altimetry. 3) Measurement of ice thickness by radio echo sounding, seismography and gravity. 4) Geomagnetic survey. 5) Measurement of snow accumulation at stakes, pits and borings. 6) Observations of surface structures and sastrugi patterns. 7) Setting of strain grids at 6 sites. 8) Triangulation and levelling for the setting of strain grid band along the parallel of 72°S (ca. 256km). 9) Observation of VLF. 10) Meteorological observation. 11) Field surveys for geology, geomorphology and glaciology in Yamato Mountains. departmental bulletin paper